Research on the Levelized Cost of Energy Reduction Method in Wind Farms Based on Enterprise Assets Management System - ZHANG Haiyang; TAN Qiming; HU Kaikai; ZHANG Jiayou (Kongzhi Yu Xinxi Jishu)
Aiming at the policy background of the comprehensive parity of wind power grid and the industry requirements for reducing the cost of electricity per kilowatt-hour, this paper implements EAM system based on Maximo platform. Through information system integration, hierarchical processing of operation and maintenance business, and wind turbine design optimization, fast response and self-learning fault handling, preventive maintenance reminder based on equipment status are implemented, and the mean time to repair(MTTR) of wind farms is reduced by 17%. Through the refined control of wind turbine data, material traceability based on serial number, standard operation and process control, dynamic adjustment of inventory based on material turnover rate has been realized, and the cost of spare parts in the wind farm inventory and the annual operation and maintenance costs(CO&M) of wind farm are reduced. This effectively reduces the levelized cost of energy in wind farms.